The transformation of PL solutions for extremely anisotropic scattering to solutions with isotropic scattering and application to the critical slab problem - Tezcan, C.; Yildiz, C. (Elsevier BV, 1993)
Abstract The PL solutions for extremely anisotropic scattering are expressed in terms of solutions for isotropic scattering. To see the use of the transformed solutions, applications for variations of the critical thickness with backward scattering are given. Numerical results are compared with the zeroth order results of elementary solutions and with the FN method.